The Influence Of Customer Relationship Management On Customer Satisfaction And Loyalty At Pusat Cantik, Pontianak City - Priskila, Priskila; Pebrianti, Wenny; Heriyadi, Heriyadi (Jurnal Multidisiplin, 2025)
This study aims to analyze the influence of Customer Relationship Management (CRM) on customer loyalty with customer satisfaction as a mediating variable at Pusat Cantik Store in Pontianak. The study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method and involves 100 respondents who are active customers of the store. The analysis results indicate that CRM has a significant influence on both customer satisfaction and customer loyalty. Furthermore, customer satisfaction is proven to have a significant impact on customer loyalty. The mediation test reveals that customer satisfaction acts as a partial mediator in the relationship between CRM and customer loyalty. This research provides a theoretical contribution to the development of customer loyalty models and practical implications for retail business actors in building and maintaining long-term relationships with customers through enhanced satisfaction.